Evaluasi Kesesuaian Lahan Untuk Berbagai Jenis Tanaman Di Lahan Gambut Kecamatan Arut Selatan Kabupaten Kotawaringin Barat - Riyandani, Devy, Ir. Taryono, M.Si, Drs. Suharjo, MS. (2016)
The research has the title "EVALUATION of the SUITABILITY of the LAND for All Variaty Plant in the Peat Landform SUBDISTRICT of ARUT SELATAN DISTRICT KOTAWARINGIN BARAT" the purpose of the research to find out the degree of suitability of the land for rice. Corn and palm oil in the area ofresearch, this research aims to know the limiting factors that affect the suitability of the land in the area of research. The method used is the method of survey sampling with data using a purposive sampling which take into consideration the specific conditions on the land that will be examined. Data collected consisted of primary data and secondary data. Primary datais the result of the analysis of the field and laboratory analysis like a potential hara,rooting, the danger of erosion/floods, salinity levels and conditions of peat. Secondary data from various agencies government agencies in West Kotawaringin Regency like a rainfall data, the data area, land use data, population data and data oncrop productivity. Processing of data by the method of matching compare between manual requirements class suitability of land for each type of plant and the characteristics of the land in the area of research. The level of compliance of land in the area of research, there are two land suitability class. The class is S3 (land suitability class marginal) and N1 (classes of land usesuitability is not appropriate at this time). For rice plant limiting factor contained insoil pH, soil drainage, slopes and nutrient elements. To plant corn, there is a limiting factor on soil pH, soil drainage, salinity. To plant oil palm there is a limiting factor onsoil drainage and soil pH. Keyword: Landform, land use, Suitability of land use and Landform peat